Active coping shields against negative aging self-stereotypes contributing to psychiatric conditions. (May 2019) - Levy, Becca R.; Chung, Pil H.; Slade, Martin D.; Van Ness, Peter H.; Pietrzak, Robert H.
Abstract: Rationale: Psychiatric conditions are often falsely considered inherent to aging. We examined whether negative age stereotypes, which older individuals tend to assimilate from the environment across their lifespan, contributed to an increased risk of developing four psychiatric conditions, and, if so, whether this risk was reduced through active coping. Method: The sample consisted of participants aged 55 years and older, free of the psychiatric conditions at baseline, drawn from the National Health and Resilience in Veterans Study, a nationally representative sample. New cases of posttraumatic stress disorder, suicidal ideation, generalized anxiety disorder, and major depressive disorder were assessed during three waves spanning a four-year period. Results: As predicted, participants holding more-negative age stereotypes were more likely to develop the psychiatric conditions, and their engagement in active coping reduced the risk of their developing these conditions. Conclusion: Our findings suggest that prevention and treatment efforts designed to reduce psychiatric conditions in later life may benefit from bolstering active coping as well as positive age stereotypes. Highlights: Negative age stereotypes predicted new psychiatric conditions among older adults. As the negativity of age stereotypes increased, risk of these conditions increased. Active coping helped protect those with negative age stereotypes from these conditions. Interventions to bolster active coping may help reduce risk of these conditions.